TREATMENT PATTERNS AND QUALITY OF LIFE OF PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION: AN EXPERIENCE OF A TERTIARY HEALTH CARE CENTERS (TREQ-AF STUDY) - Ozin, B.; Aytemir, K.; Arslan, O.; Ozcan, T.; Kanadasi, M.; Demir, M.; Oto, A. (Elsevier Science Inc, 2014)
[Abstract Not Available]